Communication and integration in the educational environment - Prieto Castillo, Daniel (2009)
The autor starts from analyz.ing the borders of formal, non formal and informal education, which are broadening to a planetary leve! due to the media culture and digital technologies.He proposes to integrare these big learning spheres through the development of crucial pedagogic experiences which involve teachers, apprentices and other community members experiencing practices based on methodologies and concepts that mark deeply each participant, and thus broadens the borders of learning.